(untitled) (Economic Journal of Nepal, 2014)
One of the most important conclusions reached by the classical economists is the Say’s Law of Markets. According to this law, production (supply) generates income, which is used completely and instantaneously to purchase (demand) commodities, so supply creates its own demand at all times. To prove his thesis, Say took a macroeconomic approach. The objective of this paper is to prove another thesis that demand creates its own supply. The arguments presented in this paper are based purely on positive economics, and the thesis is proved with the help of a simple example, and in contrast to Say’s macroeconomic approach, microeconomic approach is used to prove the thesis.